2017
DOI: 10.15676/ijeei.2017.9.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Surface Discharge Activity with Thermally Aged Nanofluid Impregnated Paper Insulating Material

Abstract: SDIV of OIP material gets altered with thermal ageing temperature of OIP material, supply voltage frequency and the harmonic content in the supply voltage. The UHF signal radiated due to surface discharges formed under AC voltage, high frequency AC voltages and with harmonic voltages, have dominant frequency at about 0.9 GHz. Surface charge accumulation studies indicate that thermal ageing have high impact on amount of charge accumulation. Also number of layers of insulation have high charge trap density, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Given that the nanofluids present a somehow different dielectric constant from the base liquids, the question that arises is whether such difference in dielectric constants (between nanofluids and air pockets or voids) renders the use of such liquids more difficult. Important work already done in relevant areas has to continue [93]. Furthermore, nanoparticle research has to be performed with vegetable derived fluids or synthetic esters, which are supposed to have a more "green" behavior (such research is being already done but it has to be intensified).…”
Section: Wwwetasrcom Danikas: Breakdown In Nanofluids: a Short Review On Experimental Results And Related Mechanismsmentioning
confidence: 99%
“…Given that the nanofluids present a somehow different dielectric constant from the base liquids, the question that arises is whether such difference in dielectric constants (between nanofluids and air pockets or voids) renders the use of such liquids more difficult. Important work already done in relevant areas has to continue [93]. Furthermore, nanoparticle research has to be performed with vegetable derived fluids or synthetic esters, which are supposed to have a more "green" behavior (such research is being already done but it has to be intensified).…”
Section: Wwwetasrcom Danikas: Breakdown In Nanofluids: a Short Review On Experimental Results And Related Mechanismsmentioning
confidence: 99%
“…They also observed the end of NF stability during the aging process, which led to the aggregation of the NPs. The surface discharge properties of aged kraft papers impregnated with MO and NF were studied by Swati et al [23], who concluded that NFs tend to accumulate a higher amount of charge and dissipate it more slowly, although the authors did not observe chemical changes in the FTIR spectrum of the samples. Another aspect that has been used to evaluate the aging process in the presence of NFs is the tensile strength of aged paper samples.…”
Section: Introductionmentioning
confidence: 99%